2007
DOI: 10.2135/cropsci2006.09.0614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trinexapac‐Ethyl Foliar Application on Creeping Bentgrass Responses to Combined Drought and Heat Stress

Abstract: Simultaneous drought and heat stress is detrimental to turfgrass growth. Growth regulators may influence plant responses to stresses. The objective of this study was to determine effects of pretreatment with trinexapac‐ethyl (TE) on creeping bentgrass (Agrostis stolonifera L.) responses to subsequent exposure to combined heat and drought stress. Plants were treated with TE (1.95 mL L−1 [v/v], Primo Maxx) every 14 d for 42 d and then exposed to combined drought and heat (35°C) in growth chambers. Application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 27 publications
10
51
0
1
Order By: Relevance
“…Increased NDVI could be related to the suppression of vertical shoot growth, which may allocate carbohydrates or energy towards tiller production as previously reported for other turfgrass species (Ervin and Koski, 1998). Similarly, in other studies with perennial ryegrass (Lolium perenne L.) and creeping bentgrass, TE application did not significantly alter osmotic adjustment during drought stress ( Jiang and Fry, 1998;McCann and Huang, 2007). Previous studies have shown that foliar application of TE delayed leaf dehydration in creeping bentgrass but had limited or no effects on osmotic adjustment under combined drought and heat stress Huang, 2007, 2008).…”
Section: Enhancement Of Drought Performance In Creeping Bentgrass Thrsupporting
confidence: 68%
“…Increased NDVI could be related to the suppression of vertical shoot growth, which may allocate carbohydrates or energy towards tiller production as previously reported for other turfgrass species (Ervin and Koski, 1998). Similarly, in other studies with perennial ryegrass (Lolium perenne L.) and creeping bentgrass, TE application did not significantly alter osmotic adjustment during drought stress ( Jiang and Fry, 1998;McCann and Huang, 2007). Previous studies have shown that foliar application of TE delayed leaf dehydration in creeping bentgrass but had limited or no effects on osmotic adjustment under combined drought and heat stress Huang, 2007, 2008).…”
Section: Enhancement Of Drought Performance In Creeping Bentgrass Thrsupporting
confidence: 68%
“…The benefits of TE applications have been previously documented in drought-stressed grasses (McCann and Huang, 2007) and in plants irrigated with saline water (Baldwin et al, 2006). In our experiment, TE had a positive effect on turf quality, especially on Princess 77.…”
Section: Discussionmentioning
confidence: 93%
“…The chemical TE has been shown to decrease tolerance to heat stress in Kentucky bluegrass (Heckman, Horst, Gaussoin, & Young, ). However, TE has also been shown to play a role in improving heat tolerance when combined with drought stress in creeping bentgrass (McCann & Huang, ). Heckman et al.…”
Section: Discussionmentioning
confidence: 99%